2009
DOI: 10.1113/jphysiol.2009.177998
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ageing on carotid baroreflex peak response latency in humans

Abstract: The stability of a physiological control system, such as the arterial baroreflex, depends critically upon both the magnitude (i.e. gain or sensitivity) and timing (i.e. latency) of the effector response. Although studies have examined resting arterial baroreflex sensitivity in older subjects, little attention has been given to the influence of ageing on the latency of peak baroreflex responses. First, we compared the temporal pattern of heart rate (HR) and mean arterial blood pressure (BP) responses to selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…However, previous studies examining the influence of age on vascular responses to sympathetic activation have reported both blunted (10) and preserved (14) responses in older individuals. In addition, the reduced BP response to carotid baroreceptor unloading may also be related to an attenuated tachycardic response (18,19). Further work is required to examine the influence of aging on the ABR-regulation of vascular conductance and the relative contribution of central hemodynamics to overall ABR control of BP.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies examining the influence of age on vascular responses to sympathetic activation have reported both blunted (10) and preserved (14) responses in older individuals. In addition, the reduced BP response to carotid baroreceptor unloading may also be related to an attenuated tachycardic response (18,19). Further work is required to examine the influence of aging on the ABR-regulation of vascular conductance and the relative contribution of central hemodynamics to overall ABR control of BP.…”
Section: Discussionmentioning
confidence: 99%
“…To accurately quantify the stimulus applied, a silicon piezoresistive pressure sensor (Freescale Semiconductor, Austin, TX) was connected to a port on the collar. To minimize respiratory-related modulation of HR, the 5-s pulses of NS and NP were delivered to the carotid sinus during a brief 12-to 15-s breath hold at end expiration phase (Eckber et al 1980;Fisher et al 2009). Familiarization sessions.…”
Section: Methodsmentioning
confidence: 99%
“…No subject had a history or symptoms of cardiovascular or pulmonary disease. There is compounding evidence to show that sex, age, and race influence carotid baroreceptor function (Credeur et al 2014;Fisher et al 2007Fisher et al , 2009Fisher et al , 2012Holwerda et al 2001Holwerda et al , 2013Kim et al 2011). Thus, in an effort to minimize these variables, each individual with MS was matched to a healthy control of the same sex, age, race, height, and weight.…”
Section: Subjectsmentioning
confidence: 99%
“…Fisher et al (9) demonstrated that the parasympathetic nervous activity blockade of the muscarinic receptors with glycopyrrolate increased the latency of the HR response of carotid baroreflex control in healthy individuals. Since our data show a marked reduction in HF component of RRi, the increased time delay observed in patients with MetS ϩ OSA (Table 3) may be associated to reduced cardiac parasympathetic modulation.…”
Section: Discussionmentioning
confidence: 99%